Perceptions of the Independence of Judges in Europe Congruence of Society and Judiciary - van Dijk, Frans (Springer Nature, 2021)
This open access book is about the perception of the independence of the judiciary in Europe. Do citizens and judges see its independence in the same way? Do judges feel that their independence is respected by the users of the courts, by the leadership of the courts and by politicians? Does the population trust the judiciary more than other public institutions, or less? How does independence of the judiciary work at the national level and at the level of the European Union? These interrelated questions are particularly relevant in times when the independence of the judiciary is under political pressure in several countries in the European Union, giving way to illiberal democracy. Revealing surveys among judges, lay judges and lawyers - in addition to regular surveys of the European Commission - provide a wealth of information to answer these questions. While the answers will not please everyone, they are of interest to a wide audience, in particular court leaders, judges, lawyers, politicians and civil servants.